(untitled) (Research, Society and Development, 2022)
Objective: to describe and delimit possible risk factors for the development of SHEG according to findings in the literature. For this research, there was a need to conduct a quantitative and qualitative revisional study based on findings in academic research platforms (VHL, LILACS, SCIELO, MEDLINE) in the years 2015 to 2020 being separated until reaching 7 articles of use. Some findings that define as risk factors maternal age, ethnicity, socioeconomic status and pre-existing pathologies such as systemic arterial hypertension, obesity diabetes and others so that it can prevent or treat in advance is the role of nursing during prenatal care to make associations with clinical history in addition to physical, biochemical tests such as plasma platelet levels, proteinuria and hematocrits. Therefore, the follow-up of the nurse who has more contact with the pregnant woman/parturient through prenatal and postpartum consultations - becomes essential, with the collaboration of the multidisciplinary team, carefully observing all the parameters indicative of SHEG and can make an early screening and the correct care with the pregnant woman affected by these pathologies contributing to the reduction of maternal-fetal mortality.